PENERAPAN KITAB TAISIRUL KHALAQ DALAM MEMBINA AKHLAK SISWA DI MTs HIDAYATUS SHOLIHIN KABUPATEN KEDIRI - Nurul Ahsin; Ervi Kumala Sari (IAIN Bone, 2022)
This study aims to determine the application of the Taisirul Khalaq book material related to the morals given at MTs Hidayatus Sholihin, the application of the Taisirul Khalaq book in building student morals, and the impact of implementing the Taisirul Khalaq book on students' morals. The type of research in this thesis is descriptive qualitative research, with the research location at MTs Hidayatus Sholihin, Gurah District, Kediri Regency. Data collection techniques through interviews, observation and documentation. Data analysis techniques used data reduction, data presentation and drawing conclusions. The results showed that, 1) All of the material contained in the Taisirul Khalaq book was taught gradually, because all the contents in the book discussed morals. 2) The application of the Taisirul Khalaq book is related to the moral learning of grade VIII MTs students at MTs Hidayatus Sholihin using various methods both inside and outside the classroom, such as exemplary, habituation, discipline, advice, and punishment. 3) The impact of the application of the Taisirul Khalaq book on the morals of the VIII grade students of MTs Hidayatus Sholihin showed that by studying the book, it makes students' morals in worship, students' morals to teachers, and students' morals in association fall into a good category.